KAJIAN TINGKAT KECELAKAAN FATAL, PENCEGAHAN DAN MITIGASI KECELAKAAN KAPAL-KAPAL PENANGKAP IKAN YANG BERBASIS OPERASI DI PPP TEGALSARI, PPN PEKALONGAN DAN PPS CILACAP - Suwardjo, Djodjo; Haluan, John; Jaya, Indra; Poernomo, Soen'an H. (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Safety performance of a fishing vessels fleet is indicated by the Fatality Accident Rate (FAR) of fishing vessels and the position of risk on F-N Curve, wether the risk position at unacceptable risk, intermediate risk or acceptable risk. The FAR of the fishing vessles, from fishing based at Tegalsari Coastal Fishing Port, Pekalongan Archipelagic Fishing Port and Cilacap Oceanic Fishing Port are 115 persons death/missing at sea per 100.000 fishermen per year and if it is compared with the FAR of the world fishing fleet, is still consider higher. Therefore, a necessary measures to reduce accident risk of fishing vessels accident with prevention and mitigation are needed. Some of the measures that we suggest to encompass the problem related to the fatal accident are: (1) training of navigation and safety competences for skippers and crew members;(2) increasing safety awareness for the fishing vessel owners, Fishing Port harbour master, fishing vessel inpectors, fisheries extension workers, instructors of fisheries education and training, community local leaders and fishermen families, (3) crews insurance, and (4) providing fishing vessel standard, ship manning standard and works in fishing standard, education, training and certification standar and standar of works in fishing.